HUBUNGAN KENDALI GLIKEMIK DENGAN ASYMMETRIC DIMETHYLARGININE PENDERITA DIABETES MELITUS TIPE 2 LANJUT USIA - Ngurah Hariawa, Kadek; Suastika, Ketut (journal of internal medicine, 2012)
Increasing life expectacy is usually in line with increasing prevalence of matabolic diseases, especially diabetes mellitus (DM). Old age and DM are risk factors for cardiovascular disease. Endothelial dysfunction is the early process of atherosclerosis. Asymmetric dimethylarginine (ADMA) is a marker for endothelial dysfunction. Until recently however, there is a lack of study on the correlation of diabetes control and ADMA in elderly with DM. The objective of this study was to assess the correlation of diabetes control with ADMA in diabetes elderly. The design of the study was cross sectional analytic study. The study subects were diabetic patients aged 60 years or above without smoking and existance of end stage renal disease. The 80 study subjects consisted of 57 males and 43 females, ages ranging from 60 to 80 years. The majority of the subjects were with other diseases i.e. hipertension 62 (77.5%), dyslipidemia 51 (63.8%), overweight 59 (73.9%), decreased renal function with creatinin clearence below 60 ml/mnt 58 (72.5%), hyperhomocysteinemia 35 (43.8%). The subjects with good glicemic control were 25 (32%), moderate 31 (38.8%), and bad glicemic control 24 (30%). Pearson correlation showed there was no correlation between glicemic control (fasting blood glucose, 2 hour after meal blood glucose, HbA1c) and ADMA. Analysis on other factors showed a correlation of ADMA with sistolic blood pressure (r=-0.222; p=0.024) and homocystein (r=0.333; p=0.001). Multiple liniar regression analysis constanly showed a correlation between homocystein and ADMA (B=0.473; p=0.003). The new construction model of this study was the formula ADMA (µmol/L)= 0.213+0.473 log homocystein µmol/L. Based on the criteria used diabetes control, we found mean difference of ADMA at systolic blood pressure (p=0.031). There was no mean diffrence of ADMA found based on the treatment regimens given i.e. those given insulin or not (p=0.547) and those given metformin or not (p=0.219). In conclusion, blood glucose control has no correlation with ADMA in the elderly with DM, however homocystein has positve correlation with ADMA in elderly with DM. The elderly with DM have several accompanying of diseases.
Keywords: ADMA, DM, elderly